Chinese classics records of the historian - Sima Qian; Wang Guozhen ([Beijing] China Intercontinental Press, 2017)
Records of the Historian is the first Chinese book on general history ever written in the biographical style. Besides,being a great literary work,Records of the Historian opens a new horizon of recording and narrating historical events in the form of individual biographies.
Keywords: Folklore -- China; Chinese fiction -- History and criticism. -- Ming Dynasty, 1368-1644.; China -- Social life and customs -- Fiction